Анализ и выбор электрохимических аккумуляторов для энергоустановок долго живущих космических аппаратов - Гасанова, В. В.; Каторгина Ю. Г.; Столяров Я. А.; Чечина Е. Г. (НТУ "ХПИ", 2014)
Проведен анализ типов аккумуляторов, используемых в энергоустановках космических аппаратов. Сформулированы рекомендации касательно выбора электрохимической системы для космических аппаратов сроком службы более 10 лет. Проведен расчет стоимости системы энергоснабжения с использованием различных типов аккумуляторов. Показано, что наиболее оптимальным, с точки зрения стоимости запуска, типом аккумуляторов являются электрохимические системы на основе лития.

This article is devoted to the analysis and selection of electrochemical energy storage for spacecrafts..The analysis of the types of batteries used in power plants spacecraft are did. The recommendations regarding the choice of an electrochemical system for spacecraft life of more than 10 years is makes. The cost of the power system by using different types of batteries is calculation. It is shown that the most optimal from the standpoint of cost trigger type electrochemical batteries are lithium-based system. While lithium-ion batteries have a high specific capacity, providing an essential resource of spacecraft. The calculation of the cost of the power system by using different types of batteries. It is shown that the most optimal from the standpoint of cost trigger type electrochemical batteries are lithium-based system.
Analysis and selection of electrochemical battaries for power plants long-lived spacecraft
Keywords: накопители энергии; система энергоснабжени; аккумуляторная батарея; космические аппараты; орбита; литий-ионные аккумуляторы; power service; accumulator; battery; spacecraft; orbit